Perspective Criticism and the Study of Narrative Biblical Literature: The Story of the Hemorrhaging Woman (Mark 5,24-34) as a Test Case - Miceli, Calogero (Théologiques, 2016)
In his recent works, Watching a Biblical Narrative : Point of View in Biblical Exegesis (2007) and Perspective Criticism : Point of View and Evaluative Guidance in Biblical Narrative (2012), Gary Yamasaki has introduced a new methodology, entitled Perspective Criticism, for analyzing biblical literature. The following paper seeks to evaluate whether or not this proposed method is a viable tool for use in the study of biblical texts. In order to do so, the account of the hemorrhaging woman (Mark 5 : 24-34) is used as a test case. In the story, the implied reader is provided with background information about the history and motivation of the hemorrhaging woman. Rather than focusing solely on the protagonist Jesus, the narrator shifts the focus of the story onto the woman and explains her unsuccessful attempts, over the years, to find a cure for her ailment. In employing the Perspective Criticism methodology, the following paper argues that the implied author has purposefully inserted this privileged information, which is achronological to the narrative time of the pericope, in order to elicit empathy from the reader with the woman. The account offers the audience the ability to see previous events from the woman’s point-of-view in order to understand her tragic struggle and emotionally connect with her inner thoughts.